DEVELOPMENT OF A TECHNOLOGY-BASED ANIMAL ELECTRONIC MEDICAL RECORD INFORMATION SYSTEM FOR ANIMAL HEALTH SERVICES - Iskandar, Dwi; Ismawatie , Emma; Nur Ibrahim , Muhammad (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
The current development of Information Technology (IT) has a huge impact on various aspects of life. This support makes it possible to send and receive information quickly without having to meet the desired person in person. The Animal Health Center (Puskeswan) is a place for providing animal health services accompanied by veterinarians and paramedics. Like humans, animals have the right to happiness in their lives. Currently, the level of animal welfare compliance remains very low. This is not only proven by government actions that have not been optimal in protecting animal rights and regulations to protect animal rights that have not been fully implemented. If patient data is recorded on a patient card, it will have negative impacts, including: Limited accessibility, possibility of data loss, human error, not environmentally friendly. An animal medical record information system is very important and useful, some of the reasons include: Efficient data management, better health care, routine care management. The research method uses the Waterfall Method system development method